Carrier Trapping by Vacancy‐Type Defects in Mg‐Implanted GaN Studied Using Monoenergetic Positron Beams. Issue 4 (27th December 2017) - Uedono, Akira; Takashima, Shinya; Edo, Masaharu; Ueno, Katsunori; Matsuyama, Hideaki; Egger, Werner; Koschine, Tönjes; Hugenschmidt, Christoph; Dickmann, Marcel; Kojima, Kazunobu; Chichibu, Shigefusa F.; Ishibashi, Shoji
Abstract : Vacancy‐type defects in Mg‐implanted GaN are probed using monoenergetic positron beams. Mg + ions are implanted to provide a 500‐nm‐deep box profile with Mg concentrations, [Mg], of 1 × 10 17 –1 × 10 19  cm −3 at room temperature. In the as‐implanted samples, the major defect species is a complex of a Ga vacancy ( V Ga ) and a nitrogen vacancy ( V N ). After annealing above 1000 °C, the major defect species is changed to vacancy clusters due to vacancy agglomeration. This agglomeration is suppressed, and the agglomeration onset temperature is decreased with a decreasing [Mg]. For samples with [Mg] ≥ 1 × 10 18  cm −3, the trapping rate of positrons by vacancy‐type defects decrease after annealing above 1100–1200 °C. This decreases is attributed to the change in the defect charge states from neutral to positive due to a downward shift of the Fermi level. The carrier trapping/detrapping properties of the vacancy‐type defects and their time dependences are also revealed. Abstract : Vacancy‐type defects in Mg‐implanted GaN are probed by means of positron annihilation. In the as‐implanted samples, the major defect species is identified as a complex of a Ga vacancy and a nitrogen vacancy. After annealing treatments, the defect species is changed to vacancy clusters due to vacancy agglomeration. Using positron annihilation and illumination technique, the carrier trapping/detrapping properties of the vacancy‐type defects are revealed.